The impact of smart cards on South African rural pensioners' lives - Nyoka, Zanele (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
E-commerce technologies have many possible applications both in commercial and non-commercial operations. The development and implementation of these applications is on the increase especially by government and its agencies, for the delivery of services. Specific to this study is the distribution of old age pension benefits to recipients that reside in the rural areas of South Africa. Of importance to this study are the factors that promote and impinge on the development, implementation and acceptance of these applications. A specific project, the Pension Biometric Project was implemented by the South African Post Office in line with the government's initiatives of improving service delivery, and in response to the encroaching digital economy. The research problem is to investigate the pensioners' perception and their experience of three areas of this project, its implementation, its acceptance and its uses and impact. The research was conducted in the constructivist paradigm, using the case study research method. Three data collection methods were used, i.e. a document study of SAPO project documentation, on-site observations and interviews with pensioners. It was found that despite problems in implementation, the pensioners were accepting of the new system, although they were ignorant of the functionalities of the smart card. Consequently, few pensioners were making use of the banking facilities of the card, or had changed their economic behaviour. The study has also found that two themes are overriding all findings of the study. These two themes are ignorance and dignity. Ignorance has had a causal effect on adoption of the smart cards and dignity has been found to be a result of the project. The overriding implication of this study is that pensioners' ignorance around issues of service delivery by government and its agencies needs to be eradicated, otherwise there is no reliable way of measuring efforts against actual delivery. Also, the fact that dignity has emerged as an overriding theme needs to be deliberately strengthened, and maybe even driven as a specified objective of the Pension Biometric Project. Recommendations in this regard are provided as well as ideas for further research.
Keywords: Old age pensioners -- South Africa -- Management; Smart cards; South African Post Office